Application of mouse model for effective evaluation of foot-and-mouth disease vaccine. Issue 33 (19th July 2016) - Lee, Seo-Yong; Ko, Mi-Kyeong; Lee, Kwang-Nyeong; Choi, Joo-Hyung; You, Su-Hwa; Pyo, Hyun-Mi; Lee, Myoung-Heon; Kim, Byounghan; Lee, Jong-Soo; Park, Jong-Hyeon
Highlights: We created FMD viruses, O, A, Asia1 serotypes which are lethal for adult C57BL/6 mice. There were no common differences among analyzed serotypes in comparing of the parental viruses and the adapted viruses. Efficacy test with various vaccines in parallel could be carried out using the mouse model. Comparison of clinical indexes from the vaccinated/challenged mice was shown dose-dependent effect. Abstract: Efficacy evaluation of foot-and-mouth disease (FMD) vaccines has been conducted in target animals such as cows and pigs. In particular, handling FMD virus requires a high level of biosafety management and facilities to contain the virulent viruses. The lack of a laboratory animal model has resulted in inconvenience when it comes to using target animals for vaccine evaluation, bringing about increased cost, time and labor for the experiments. The FMD mouse model has been studied, but most FMD virus (FMDV) strains are not known to cause disease in adult mice. In the present study, we created a series of challenge viruses that are lethal to adult C57BL/6 mice. FMDV types O, A, and Asia1, which are related to frequent FMD outbreaks, were adapted for mice and the pathogenesis of each virus was evaluated in the mouse model. Challenge experiments after vaccination using in-house and commercial vaccines demonstrated vaccine-mediated protection in a dose-dependent manner. In conclusion, we propose that FMD vaccine evaluation should be carried out using mouse-adapted challenge viruses as a swift, effective efficacy test of experimental or commercial vaccines.